Manajemen Pembelajaran Anak Berkebutuhan Khusus (ABK) pada SD Negeri 8 Bula Kecamatan Bula Kabupaten Seram Bagian Timur - Rumatumia, Hairudin; Kempa, R.; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Education is a basic right for everyone, regardless of social class/strata, race, political choice, creed or physical and mental differences as stated in the 1945 Constitution article 31 paragraph (1) states "Every citizen has the right to equal educational opportunities". Law Number 4 of 1997 concerning persons with disabilities Article 10 Paragraph (1) states that "Equality of opportunity for persons with disabilities in all aspects of life and livelihood is implemented through the provision of accessibility". The existence of children with special needs (ABK) at SD Negeri 8 Bula, Bula District, East Seram Regency consists of several categories including: Special Smart Children and Special Talents (CIBI), Slow learners, Children who have specific learning difficulties, and Autism. In the application of learning management at SD Negeri 8 Bula, of course, it must be slightly different from other public schools that do not have students with special needs ABK). In education, management is the activity of integrating educational resources to be centralized in an effort to achieve predetermined educational goals by directing people to carry out certain activities to achieve goals. That is, moving those people to organize the means, materials, tools, and costs and by certain methods carry out their respective activities. In practice the manager or principal is in charge of directing the teachers, staff, and students. Not only leading or encouraging, but also thinking about strategies or policies to regulate school physical, facilities, and infrastructure. This type of research is qualitative descriptive research Through. From the results of the research conducted, it was found that the Planning for Learning Management of Children with Special Needs (ABK) carried out by the Principal and Teachers / Educators at SD Negeri 8 Bula in identifying students must be carried out earlier when students register so that in the preparation of RPP and Syllabus a modified curriculum can be made that can accommodate learning models for students with special needs, Implementation (Actuating) of Learning Management of Children with Special Needs (ABK) at SD Negeri 8 Bula, Principals and Teachers have implemented learning strategies in accordance with references to the applicable curriculum, namely the 2013 Curriculum, and Evaluation of Learning Management of Children with Special Needs (ABK) at SD Negeri 8 Bula, Principals and Teachers evaluate the implementation of learning, evaluations are carried out on student learning outcomes common.